A WLAN-oriented distributed hierarchical parallel simulation method - JIA Wenfei; YANG Mao; YAN Zhongjiang; LI Bo (Xibei Gongye Daxue Xuebao)
To solve the problem that the efficiency decreases with the increase of terminal nodes in wireless local area network(WLAN) distributed parallel simulation, a WLAN-oriented distributed hierarchical parallel simulation method is proposed. Firstly, considering the WLAN star network topology, the process of the simulated access point (AP) is denoted as the main process, which is responsible for time synchronization with the other processes of the simulated station (STA) nodes in the WLAN network. Secondly, the processes of all simulated STAs are then evenly divided into groups, and the group leader is responsible for the synchronization of processes within the group. Then, after the main process broadcasts the simulation start event, the group leader process firstly collects the end message of the group member's terminal node, and then reports to the main process. A three-layer hierarchical structure is constructed, consisting of the main process layer, the group leader process layer and the group member process layer. Finally, the time gain factor of the hierarchical simulation method is analyzed and obtained in closed-form expression, under the different computational loads. Simulation results show that comparing to the existing non-hierarchical simulation method, when the average computational load is 1.2x time unit and the nodes number is 100, the gain of the proposed method can reach 50%.